2011
DOI: 10.5468/kjog.2011.54.11.659
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate gonadotropin secretion in polycystic ovary syndrome: The relationship with clinical, hormonal and metabolic characteristics

Abstract: ObjectiveTo evaluate the clinical, hormonal and metabolic characteristics according to luteinizing hormone (LH)/follicle stimulating hormone (FSH) ratio in women with polycystic ovary syndrome (PCOS). MethodsA total of 225 women with PCOS were included in this study. They were divided into two groups according to LH/FSH ratio; group A (LH/FSH < 2, n=160) and group B (LH/FSH > 2, n=65). We compared clinical, hormonal and metabolic characteristics including age at menarche, body mass index (BMI), blood pressures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 24 publications
2
8
5
Order By: Relevance
“…Sikka et al [25] reported that ovarian volume positively correlates with the LH/FSH ratio and WHR, and their finding is partially consistent with our results. In contrast, a previous study conducted in Korea [16] reported that WHR was significantly lower in PCOS women with LH/FSH ratios >2, and this finding differs from the results of our study. In the present study, no significant difference was observed in BMI among the three groups.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Sikka et al [25] reported that ovarian volume positively correlates with the LH/FSH ratio and WHR, and their finding is partially consistent with our results. In contrast, a previous study conducted in Korea [16] reported that WHR was significantly lower in PCOS women with LH/FSH ratios >2, and this finding differs from the results of our study. In the present study, no significant difference was observed in BMI among the three groups.…”
Section: Discussioncontrasting
confidence: 99%
“…However, after adjustments for age and BMI, a correlation between the total cholesterol level and the LH/FSH ratio was observed. Our finding is in disagreement with the results of Shim et al [16], which reported that the high density lipoprotein level, not the total cholesterol level, was significantly different according to the LH/FSH ratio. It is hard to explain the rationale of the relationship between the total cholesterol level and LH/FSH ratio in the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations